Role of neutrophil chemoattractant CXCL5 in SARS-CoV-2 infection-induced lung inflammatory innate immune response in an in vivo hACE2 transfection mouse model - Yan Liang (Zoological Research, 2020)
Understanding the pathogenesis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and clarifying antiviral immunity in hosts are critical aspects for the development of vaccines and antivirals. Mice are frequently used to generate animal models of infectious diseases due to their convenience and ability to undergo genetic manipulation. However, normal adult mice are not susceptible to SARS-CoV-2. Here, we developed a viral receptor (human angiotensin-converting enzyme 2, hACE2) pulmonary transfection mouse model to establish SARS-CoV-2 infection rapidly in the mouse lung. Based on the model, the virus successfully infected the mouse lung 2 days after transfection. Viral RNA/protein, innate immune cell infiltration, inflammatory cytokine expression, and pathological changes in the infected lungs were observed after infection. Further studies indicated that neutrophils were the first and most abundant leukocytes to infiltrate the infected lungs after viral infection. In addition, using infected CXCL5-knockout mice, chemokine CXCL5 was responsible for neutrophil recruitment. CXCL5 knockout decreased lung inflammation without diminishing viral clearance, suggesting a potential target for controlling pneumonia.